1991
DOI: 10.3354/meps075109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and abundance of larval and juvenile fish, chlorophyll and macrozooplankton around the Mississippi River discharge plume, and the role of the plume in fish recruitment

Abstract: In September 1986, we collected neuston (1 x 2 m, 0.947 mm mesh) and surface chlorophyll a samples and hydrographic data at 46 stations around the discharge plume of the Mississippi River. Transects were positioned so that the 3 water masses in the plume area -plume water, Gulf of Mexico shelf water and frontal water (a mixture of the former 2) -were sampled. The plume was represented by a shallow lens of water < 3 4 '10 salinity and < 29 "C resting atop warmer (> 29 "C) and more saline (> 34 %) Gulf of Mexico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 26 publications
(32 reference statements)
5
78
0
1
Order By: Relevance
“…The presence of penguins in productive waters is in line with several studies that found that seabirds forage in areas of elevated levels of primary productivity (Weimerskirch et al, 2004;Ainley et al, 2005;Suryan et al, 2012). Areas with high Chl-a content are associated with sustained primary productivity and are therefore more likely to attract and aggregate planktivores that in turn provide predictable food sources for planktivorous fish and their predators (Grimes and Finucane, 1991;Ressler et al, 2005;Scales et al, 2014).…”
Section: Environmental Differences Between the Foraging Range And Nonsupporting
confidence: 59%
See 2 more Smart Citations
“…The presence of penguins in productive waters is in line with several studies that found that seabirds forage in areas of elevated levels of primary productivity (Weimerskirch et al, 2004;Ainley et al, 2005;Suryan et al, 2012). Areas with high Chl-a content are associated with sustained primary productivity and are therefore more likely to attract and aggregate planktivores that in turn provide predictable food sources for planktivorous fish and their predators (Grimes and Finucane, 1991;Ressler et al, 2005;Scales et al, 2014).…”
Section: Environmental Differences Between the Foraging Range And Nonsupporting
confidence: 59%
“…Entrainment of phytoplankton and zooplankton attract foraging fish, making estuarine plume fronts important nearshore foraging features for marine predators, particularly seabirds (Grimes and Kingsford, 1996;Skov and Prins, 2001;Zamon et al, 2014). However, the dynamic nature of these water masses result in large physical and physico-chemical fluctuations (e.g., temperature, salinity and dissolved oxygen), which influence local prey distribution, composition and biomass (Grimes and Finucane, 1991;Wagner and Austin, 1999). This variability has subsequent effects on the distribution of marine predators, whose at-sea distribution is mostly controlled by the occurrence of their prey as well as their physiological and breeding energetic constraints (Wakefield et al, 2009;Zamon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An unusually large summer bloom (up to 73 μg chl L −1 ) was observed in this region (Stn S12), accompanied by a drawdown of PO 4 to limiting concentrations (Xu et al 2009). The frontal region of the plume has also been found to have high chl a concentrations relative to inshore and offshore waters in other coastal waters such as Chesapeake Bay (Breitburg 1990;Harding 1994) and the Mississippi River plume (Grimes and Finucane 1991).…”
Section: Spatial Variabilitymentioning
confidence: 99%
“…There is large spatiotemporal variability in oceanographic conditions, with the Gulf of Mexico influenced greatly by inflows and discharges from rivers and other land-based sources, including the Mississippi River, and by large-scale oceanographic features, such as the Loop Current and associated core eddies of different thermal conditions (Govoni and Grimes 1992; Sturges and Leben 2000). Combined, these factors result in large spatiotemporal variability in physicochemical conditions, causing primary production to vary markedly within and across areas of different oceanographic conditions in the Gulf of Mexico (Grimes and Finucane 1991;Biggs 1992). Physical-chemical variability affects the distribution, growth, and mortality of pelagic larvae of many fish species in the Gulf of Mexico (Govoni et al 1989;DeVries et al 1990;Lang et al 1994).…”
Section: Overview Of the Gulf Of Mexico Ecosystem For Finfishmentioning
confidence: 99%